Designing a Progressive Model of Cohort-Based Programming - Will Ashford (Adult Education Research Conference, 2013)
This research identified how faculty were able to use a progressive model of cohort-based programming to intentionally increase the success of underrepresented student groups in higher education (Cunningham, P. 1994, 1996, 2003). In addition the essences of the model are detailed.